Epilepsy-Risk Factor For The Periodontal Disease - Liliana Pasarin; Ioana Rudnic; Irina Ursarescu; Sorina Solomon; Silvia Martu (Romanian Society of Oral Rehabilitation, 2013)
Introduction The epilepsy patients are affected not only by the medical aspects of the disease but also by adjacent aspects of psychosocial and economic nature, with important implications on the quality of life on epilepsy subjects. Aim of the study The purpose of the study was to make an evidence on the differences between non-epileptic and epileptic patients concerning the oral health, insisting on the odontal-periodontal status. Materials and methods The study was conducted on 202 subjects divided in two groups-101 subjects with epilepsy, 101 without epilepsy on which we realized a thorough anamnesis (with data of associated drugs, oral hygiene-the brushing frequency, dental visits and dental prosthetic treatments) and a clinical examination. Results The patients without a controlled disease, with frequent, generalized episodes, present an improper oral status comparing to those in the control group. We did not notice secondary effects related to the phenytoin medication. Conclusions Our study demonstrates that the epileptic patients present a critical oral health comparing to the non-epileptic patients.